Focus on nicotine and caffeine - Perry Robert L 1950; Neuhaus, David (Frederick, Md. : Twenty-first Century Books, 1990)
Describes the history, effects, social aspects, and physical dangers of using tobacco and caffeine products.
Includes index.
Keywords: Tobacco use -- United States -- Juvenile literature; Smoking -- United States -- Juvenile literature; Caffeine -- Juvenile literature; Smoking; Caffeine; Drugs